Development and preliminary evaluation of a pediatric Spanish/English speech perception task - Calandruccio, Lauren (Am J Audiol, 2014)
PURPOSE: To develop a task to evaluate children’s English and Spanish speech perception abilities in either noise or competing speech maskers. METHODS: Eight bilingual Spanish/English and eight age matched monolingual English children (ages 4.9 –16.4 years) were tested. A forced-choice, picture-pointing paradigm was selected for adaptively estimating masked speech reception thresholds. Speech stimuli were spoken by simultaneous bilingual Spanish/English talkers. The target stimuli were thirty disyllabic English and Spanish words, familiar to five-year-olds, and easily illustrated. Competing stimuli included either two-talker English or two-talker Spanish speech (corresponding to target language) and spectrally matched noise. RESULTS: For both groups of children, regardless of test language, performance was significantly worse for the two-talker than the noise masker. No difference in performance was found between bilingual and monolingual children. Bilingual children performed significantly better in English than in Spanish in competing speech. For all listening conditions, performance improved with increasing age. CONCLUSIONS: Results indicate that the stimuli and task are appropriate for speech recognition testing in both languages, providing a more conventional measure of speech-in-noise perception as well as a measure of complex listening. Further research is needed to determine performance for Spanish-dominant listeners and to evaluate the feasibility of implementation into routine clinical use.